Executive recruiting for dummies - Perry, David E., 1960-; Haluska, Mark J., 1956- (Tantor Media, 2020)
Recruiting for high-end executives requires a special skill-set, and Executive Recruiting For Dummies is here to help you add this niche talent to your arsenal. Whether you're an in-house human resources manager or a professional recruiter at a search firm, this friendly guide walks you through each step of filling that senior, executive, or other highly specialized position. This book covers the globalization of talent and the advantages of executive recruiting. It provides expert guidance on finding the right candidates, conducting hardy screening and interviewing processes, closing deals, and more.There are 10,000,000 businesses in America that hire at least one senior executive a year, and most turn to commissioning a third-party organization, such as an executive search firm. Rather than losing that next top-tier recruiting job, let Executive Recruiting For Dummies show you how to add this highly desirable and sought-after skill to your resume.Learn to recruit with precision; create a robust interview process; close the deal with a winning offer; and find out how to work with professional recruiters. Discover how to find the best talent and retain and attract clients with the help of Executive Recruiting For Dummies.